Evapo-transpiration, water and radiation-utilization of clusterbean (Cyamopsis tetragonoloba) - RAO, A S; SINGH, R S; JOSHI, N L; RAMAKRISHNA, Y S (The Indian Journal of Agricultural Sciences, 2013)
The evapotranspiration rate of unstressed ’Maruguar’ clusterbean (Cyamposis tetragonoloba (L)Taubert) in an arid region at Jodhpur was 2.3-3.9 mm/day during early growth, 6.3-9.3mm/day at peak vegetative stage,5.3-5.8 mm/day at flowering/pod formation stage and 1.2-4.2 mm/day at maturity stage.The crop coefficient (ratio of actual to potential evapotranspiration) was 0.42-0.58 at early growth stage,0.62-1.17 at peak vegetative stage,0.70-1.05 flowering and pod formation stages and declined to 0.43-0.60 at maturity. Irrigation enhanced seed yield of clusterbean by 123% at 50% rate and 180% at 100% rate of water application from that of rain fed crop. Ther water-use efficiency of the crop varied from 1.47 to 4.10 kg/ha/mm and the radiation-use efficiency for unit dry matter production of intercepted photosynthetically active radiation was 0.57-1.21 g/MJ under rainfed to 1.42-2.31 g/MJ under irrigated condition. Advection enhanced evapotranspiration of clusterbean by 50-78%.